2015
DOI: 10.1038/srep16678
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Loads Flowing into Coastal Waters from the Main Rivers of China (2006–2012)

Abstract: Based on monthly monitoring data of unfiltered water, the nutrient discharges of the eight main rivers flowing into the coastal waters of China were calculated from 2006 to 2012. In 2012, the total load of NH3-N (calculated in nitrogen), total nitrogen (TN, calculated in nitrogen) and total phosphorus (TP, calculated in phosphorus) was 5.1 × 105, 3.1 × 106 and 2.8 × 105 tons, respectively, while in 2006, the nutrient load was 7.4 × 105, 2.2 × 106 and 1.6 × 105 tons, respectively. The nutrient loading from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(63 citation statements)
references
References 29 publications
1
62
0
Order By: Relevance
“…Inputs of particulate nitrogen and phosphorus and dissolved silica declined due to damming of rivers, notably the construction of the Three Gorges Dam on the Chang Jiang. As opposed to the recently declining or stable nutrient loads from large rivers in Europe and North America, nitrogen and phosphorus discharges monitored from the eight main rivers flowing into the coastal waters of China increased by 40 and 75%, respectively, from 2006 to 2012 (Tong et al, 2015). While nearly half of the dissolved nitrogen and virtually all of the dissolved phosphorus loads to the Bohai Gulf in 2000 originated from human sewage, almost all of the dissolved nitrogen and nearly half of the dissolved phosphorus inputs to seas to the south emanate from agricultural sources or, in the case of nitrogen, atmospheric deposition (Strokal et al, 2014).…”
Section: Asiamentioning
confidence: 87%
“…Inputs of particulate nitrogen and phosphorus and dissolved silica declined due to damming of rivers, notably the construction of the Three Gorges Dam on the Chang Jiang. As opposed to the recently declining or stable nutrient loads from large rivers in Europe and North America, nitrogen and phosphorus discharges monitored from the eight main rivers flowing into the coastal waters of China increased by 40 and 75%, respectively, from 2006 to 2012 (Tong et al, 2015). While nearly half of the dissolved nitrogen and virtually all of the dissolved phosphorus loads to the Bohai Gulf in 2000 originated from human sewage, almost all of the dissolved nitrogen and nearly half of the dissolved phosphorus inputs to seas to the south emanate from agricultural sources or, in the case of nitrogen, atmospheric deposition (Strokal et al, 2014).…”
Section: Asiamentioning
confidence: 87%
“…Inputs of total dissolved N and P to Chinese rivers by source at the sub-basin scale are quantified. Here, the study area covers the six main rivers (Tong et al 2015). These are the Yellow, Hai, Liao, Yangtze, Huai and Pearl ( for the rural population ) and of Morée et al (2013) for the urban population.…”
Section: Study Area and Methodologymentioning
confidence: 99%
“…In general, these studies confirm an increase in fluxes of dissolved nutrients by rivers since the 1970s, except for Powers et al (2016) who showed a declining trend in P export by the Yangtze since 1970. Some experimental studies also report on nutrient pollution problems for inland water systems (Huang 2015;Xu et al 2014) and estuaries (Liu et al 2009b;Tong et al 2015). For example, Xu et al (2014) indicate that many Chinese rivers like Huai, Hai, Yellow and river deltas today have concentrations of nutrients at levels that do not allow for human consumption.…”
Section: Trends In Nutrient Export By Riversmentioning
confidence: 99%
See 2 more Smart Citations